2021
DOI: 10.1016/j.ijheatmasstransfer.2020.120481
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of thermal phenomena during cavitation through an orifice

Abstract: Thermal properties of cryogenic fluids can profoundly change the nature of cavitation since the fluid pressure drop is not, anymore, the only driving parameter of this phenomenon.In this research, we have conducted experiments inducing cavitation via a cylindrical orifice using Liquid Nitrogen as working fluid and exploring cavitation regimes going from bubbly cavitation to full flashing. Among others, we performed unsteady pressure measurements to derive the speed of sound during cavitation and high-speed ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In case of cryogenic fluid, the approximation P min ∼ P sat can fail, since the thermodynamic state strongly influences both the cavitation occurrence and its regime [8] and the fluid temperature varies during the phase change. Therefore, to correctly describe the phenomenon, two more parameters must be considered, i.e., the subcooling degree ∆T sub and the superheat R p :…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In case of cryogenic fluid, the approximation P min ∼ P sat can fail, since the thermodynamic state strongly influences both the cavitation occurrence and its regime [8] and the fluid temperature varies during the phase change. Therefore, to correctly describe the phenomenon, two more parameters must be considered, i.e., the subcooling degree ∆T sub and the superheat R p :…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…However, it is more common in the literature to find publications analysing the issue of cavitation supported by experimental studies with the fluid flowing in the cylindrical orifice area for low or high-pressure values 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Abbas et al found that the absorption coefficient of the drilling tool affected the cutting temperature by simulating the heat distribution of twist drill pipe drilling. When the cutting edge breaks hard rock, most of the cutting work is converted into cutting heat, resulting in a rapid increase in bit temperature . Srimaruthi et al systematically studied the influence of bit design parameters on cutting temperature and concluded that the bit screw angle, the drilling location, and lithology had a significant impact on the increase of temperature caused by the clog of the drain hole.…”
Section: Introductionmentioning
confidence: 99%